Questioning Islamic Belief in Post-Genocide Bangladesh: Mu‘tazilites and Ash‘arites, Maya and Sohail - Swazo, Norman Kenneth (Holocaust and genocide studies, 2018)
The civil war of 1971 between then West Pakistan and East Pakistan led to the formation of the new nation-state of Bangladesh—and to ongoing contestation about war crimes, crimes against humanity, and genocide. Many locals who once collaborated with the Punjabi-dominated Pakistani military have in recent years been held accountable before war crimes tribunals, including at least one prominent Islamist hanged. The crimes of 1971 included ethnic cleansing of Bengali Hindus and the mass murder of Bengali Muslims whose South Asian culture was identified as so reflective of Hindu influence as to be heretical.